Pengaruh Pelatihan Kerja dan Motivasi Kerja Terhadap Kinerja Karyawan Produksi Pada PT. Alasindo Prima di Tangerang - Shinta Audia; Abdul Gani Sidqi; Feriadi Feriadi (eCo-Buss, 2023)
This study aims to determine the effect of work training and work motivation on employee performance at PT. Alasindo Prima. Job training at PT. Alasindo Prima has a significant influence on employee performance based on employee perceptions as seen from the t test results of tcount 5.079 > ttable 2.000 and sig value (0.00) <0.05. In testing the coefficient of determination Job training has a low influence on employee performance by 55.5% and the remaining 45.5% is influenced by other factors.Work motivation at PT. AlasindoPrima has a significant influence on employee performance as seen from the results of the tcount test, 7.623 > ttable 2.000 and the sig value (0.00) <0.005. In testing the coefficient of determination, work motivation has an influence on employee performance by 70.7% and the remaining 29.3% is influenced by other factors.Training and work motivation at PT. Alasindo Prima has a simultaneous significant effect on employee performance as seen from the results of the F test of Fcount 28.886 > Ftable 2.77 Training and work motivation have an influence on employee performance of 70.9% while the remaining 29.1% is influenced by other factors this is seen in the coefficient of determination test.